1994
DOI: 10.1080/00150199408245095
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of magnetic structure and phase transitions in Co311B7O13Br boracite by neutron diffraction

Abstract: Neutron diffraction investigations of orthorhombic Co 3 11 B 7 0 13 Br at 293 K and in the temperature range 1.5-30 K revefl a two step onset of magnetic ordering, starting at the the second order transition to a weakly ferromagnetic phase at TN = 17.5 K (Nee( type) and followed at about T, = 10.5 K, by a smooth transformation to a three-dimensional canted magnetic structure (magnetic space group Pc'a2,'(Shl~'), magnetic modes Cx( + + --), F,( ++++),A,(+ --+ ). The three Co sites display completely different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Neutron diffraction studies on Co 3 11 B 7 O 13 Br [181] revealed a two-step onset of magnetic ordering, starting at the second-order PT at T N = 17.5 K and followed below about T = 10.5 K by a smooth transformation to a threedimensionally canted magnetic structure of space group P c a2 1 . The transformation coincides with a minimum of magnetic birefringence n γ,β (T ) at ≈10 K and with a maximum of the ME coefficient α 32 at 10 K [177].…”
Section: B Co 3 B 7 O 13 Brmentioning
confidence: 97%
See 1 more Smart Citation
“…Neutron diffraction studies on Co 3 11 B 7 O 13 Br [181] revealed a two-step onset of magnetic ordering, starting at the second-order PT at T N = 17.5 K and followed below about T = 10.5 K by a smooth transformation to a threedimensionally canted magnetic structure of space group P c a2 1 . The transformation coincides with a minimum of magnetic birefringence n γ,β (T ) at ≈10 K and with a maximum of the ME coefficient α 32 at 10 K [177].…”
Section: B Co 3 B 7 O 13 Brmentioning
confidence: 97%
“…These anomalies are also reflected in other physical properties, for which we compile data in Table III. Neutron diffraction has been performed on 11 B enriched polycrystalline samples of Co-Cl [180], Co-Br [181], and Co-I [149].…”
Section: Cobalt Boracitesmentioning
confidence: 99%
“…For M = Co and X = Br, despite the presence of the expected large orbital momentum contribution, the third site exhibits a magnetic moment of 1.7(1) µ B while the other 2 show respectively a magnetic moment of 4.7(2) and 4.0(2) µ B . 14 For Mn 3 B 7 O 13 I, only one site shows a saturated magnetic moment with 5.4(2) µ B while the other two sites are reported with a magnetic moment of 3.8(2) µ B . 12 Similar results are reported for the other compositions investigated by neutron diffraction.…”
Section: A Structural Propertiesmentioning
confidence: 93%
“…These results are in contrast with the reported literature on the magnetic ground state of the boracites. 8,[12][13][14][15] Fe 3 B 7 O 13 (OH) crystallizes in the trigonal space group R3c which is potentially ferroelectric but does not exhibit any weak ferromagnetic component in contrast to all the other reported boracites. 8 Even Co 3 B 7 O 13 Cl which also exhibits the trigonal symmetry R3c at room and low temperature, changes of symmetry giving rise to a weak ferromagnetic component below T N = 12 K. 25 It would be of interest to investigate the other compositions exhibit the trigonal R3c symmetry (X = OH, NO 3 for instance) at room temperature in order to investigate further whether Fe 3 B 7 O 13 (OH) is the exception to the rule or not.…”
Section: A Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation